Disasters and social reproduction : crisis response between the state and community - Illner, Peer (Mapping social reproduction theory, 2021)
"Many communities in the United States have been abandoned by the state. What happens when natural disasters add to their misery? This book looks at the broken relationship between the federal government and civil society in times of crises. Mutual aid has gained renewed importance in providing relief when hurricanes, floods and pandemics hit, as cuts to state spending put significant strain on communities struggling to survive. Harking back to the self-organised welfare programmes of the Black Panther Party, radical social movements from Occupy to Black Lives Matter are building autonomous aid networks within and against the state. However, as the federal responsibility for relief is lifted, mutual aid faces a profound dilemma: do ordinary people become complicit in their own exploitation? Reframing disaster relief through the lens of social reproduction, Peer Illner tracks the shifts in American emergency aid, from the economic crises of the 1970s to the Covid-19 pandemic, raising difficult questions about mutual aid's double-edged role in cuts to social spending. As sea levels rise, climate change worsens and new pandemics sweep the globe, Illner's analysis of the interrelations between the state, the market and grassroots initiatives will prove indispensable."--